Indeks Massa Tubuh dengan Kadar Hb-A1c pada Pasien Diabetes Melitus Tipe II - Irman Saputra; Firhat Esfandiari; Esteria Marhayuni; M Nur (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Backgrounds :Excess weight is a situation that is almost close to obesity, where a person can be declared overweight if the person has a BMI ≥ 23. Excessive fat deposits in the body of patients with excess weight or obesity can lead to insulin resistance which affects the patient's blood sugar and have a risk of1,71 times developing levels diabetes melitus. Without weight loss and lifestyle modification, people with metabolic syndrome have a significant risk of becoming type 2 diabetes melitus. Purpose:To find out the relationship between body mass index with Hb-A1c in patients FKTP diabetes melitus type 2 in independent practice doctor K. Hakikiyah Central Lampung. Methods:This study is an analytical study and used Cross Sectional Approach, the population in this study is the patients FKTP diabetes melitus type 2 in independent practice doctor K. Hakikiyah Central Lampung. Sampling methods used the total sampling with a total of 56 people. Data analysis was done by univariate and bivariate analysis with spearman test. Results:Result showed that the most BMI Body Mass Index was in overweight category with total of 30 people (53,6%). The highest frequency distribution of Hb-A1c levels is the highest category of 40 people (71,4%). It was found that there was a relations between Body Mass Index (BMI) with Hb-A1c in patients FKTP diabetes mellitus type 2 in independent practice doctor K. Hakikiyah Central Lampung, with p-value = 0.000, r = 0,600. Conclusion:It is known that there is a relationship between Body Mass Index (BMI) with Hb-A1c in patients FKTP diabetes melitus type 2 in independent practice doctor K. Hakikiyah Central Lampung August 2019. Keyword : body mass index (BMI), Hb-A1c, diabetes melitus tipe 2.